2007
DOI: 10.1111/j.1741-3737.2007.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Partnership Instability and Child Well‐Being

Abstract: We use data from three waves of the Fragile Families Study (N= 2,111) to examine the prevalence and effects of mothers’ partnership changes between birth and age 3 on children’s behavior. We find that children born to unmarried and minority parents experience significantly more partnership changes than children born to parents who are married or White. Each transition is associated with a modest increase in behavioral problems, but a significant number of children experience 3 or more transitions. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
369
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(393 citation statements)
references
References 69 publications
17
369
0
4
Order By: Relevance
“…It is more likely subsequent to a parental divorce (condition 1) and is associated with high levels of parenting stress and lower-quality parent-child relationships leading to lower attainment among children (condition 2) (Beck et al 2010;Cavanagh, Crissey, and Raley 2008;Cavanagh and Huston 2006;Halpern-Meekin and Turney 2016;Lee and McLanahan 2015;Osborne and McLanahan 2007;Thomson and McLanahan 2012;Waldfogel, Craigie, and Brooks-Gunn 2010;Wu and Martinson 1993;Wu and Thomson 2001). Instability is likely to vary across families.…”
Section: Mediating Effects Of Parental Divorce On Children's Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more likely subsequent to a parental divorce (condition 1) and is associated with high levels of parenting stress and lower-quality parent-child relationships leading to lower attainment among children (condition 2) (Beck et al 2010;Cavanagh, Crissey, and Raley 2008;Cavanagh and Huston 2006;Halpern-Meekin and Turney 2016;Lee and McLanahan 2015;Osborne and McLanahan 2007;Thomson and McLanahan 2012;Waldfogel, Craigie, and Brooks-Gunn 2010;Wu and Martinson 1993;Wu and Thomson 2001). Instability is likely to vary across families.…”
Section: Mediating Effects Of Parental Divorce On Children's Outcomesmentioning
confidence: 99%
“…It is telling that the educational attainment among high propensity children is unaffected by parental divorce, suggesting that social discourse and policy aimed at promoting martial stability among disadvantaged families, without attending to socioeconomic and family conditions in which adverse events are expected, is misguided. yet such children continue to be more disadvantaged relative to children born to marital unions (Osborne and McLanahan 2007). If cohabitating unions are more disadvantaged and unstable from the onset than marital unions, the effects of dissolution on children may be less severe (Brown 2006;McLanahan, Tach, and Schneider 2013).…”
Section: Sensitivity Analysis For Heterogeneous Total and Mediating Ementioning
confidence: 99%
“…As suggested by previous research, the creation of a stable family environment is critical for children (Osborne & McLanahan, 2007;Sun & Yuanzhang, 2008). However, partnership and family stability cannot be achieved without considering women"s perceptions and experiences of multiple partnership transitions.…”
mentioning
confidence: 99%
“…Negative outcomes include behavioral problems, delinquency, and teenage pregnancy (Cavanagh & Huston, 2006;Fomby & Cherlin, 2008;Wu & Thomson, 2001). Osborne and McLanahan (2007) reported that each partnership transition modestly increased the likelihood of a child exhibiting behavioral problems. Even one partnership transition, such as a separation, introduces multiple stressors into family life, which could include changes in family rules and routines, reassignment of household roles and responsibilities, challenges in meeting the emotional needs of family members, and readjustment of family finances.…”
mentioning
confidence: 99%
See 1 more Smart Citation